Planning approval of housing developments: case study of the city of Johannesburg and Tshwane metropolitan municipalities of South Africa - Buthelezi, Nonhlanhla B. C.; Onatu, George O.; Aigbavboa, Clinton O. (Frontiers in Sustainable Cities, 2025)
Planning approval of housing developments is one of the highly regulated sectors in the world. The Republic of South Africa (RSA), just like other countries, has set broad spatial planning frameworks that have become a useful guideline for planning approvals. Various scholars have noted that some of these spatial planning policies are very weak in terms of addressing the real structure of the economy and housing challenges but instead have rather focused on check listing and implementing policy visions based only on the social, political, and institutional regulatory environments. The post Covid Reconstruction era has brought life back into the spatial planning policy debates to go beyond issues of weak institutions, internal processes but to focus more on job creation to reduce unemployment, poverty, increase production and related agglomeration economic benefits that come with people and firms located near to one another. The problem emanating from this is that several of the planning approvals processes for housing developments have been fraught with delays and hindrances such that their contributions to rapid economic growth are negligible and invisible. Hence, this research is to find out to what extent have the planning approval processes of housing development in both the City of Johannesburg and Tshwane experienced delays that impact on the regional economic growth? Since South Africa is a home to 62 million people and has more than 4,075 unplanned settlements that require planning approvals. This research is based on document content analysis and case study design. A sample of 25 practitioner’s, professionals in the two metropolitan municipalities and government departments were involved. The conclusion drawn and findings of the research point to the need for collaborative planning approval reform and approaches that are nationally acceptable and digitized systems to monitor the trends in planning approvals.